FEMALE EMIGRATION. FROM RURAL ROMANIA TO THE ADRIATIC COAST: WOMEN ON THEIR JOURNEY BETWEEN OPPORTUNITY AND SOCIAL VULNERABILITY. “THE ITALIAN SYNDROME” - BURTINI, Dino (Studia Universitatis Babeș-Bolyai Geographia, 2015)
Female Emigration. From Rural Romania to the Adriatic Coast: Women on Their Journey between Opportunity and Social Vulnerability. “The Italian Syndrome”. The twenty-first century can be called the “age of migration”, in fact since the de-colonization and markedly since the eighties migration affects the entire planet, qualifying as a global phenomenon. Comparing it with it in the past today prevails new elements and in fact, in addition to a geographical change of the phenomenon, it has turned its composition, showing a growing feminization.